The effect of the implementation of e-government and bureaucratic accountability on the level of public trust in public services in ambon city - Mike J. Rolobessy (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
This study examines the influence of e-government implementation and bureaucratic accountability on public trust in public services in Ambon City. Digital transformation in governance requires transparent, efficient, and accountable systems to build public trust. A quantitative approach with a survey design was used, involving 400 respondents selected through proportionate stratified random sampling. Data were collected using a structured questionnaire with a 5 point Likert scale and analyzed using multiple linear regression. The results show that e-government implementation positively and significantly affects public trust, with a regression coefficient of 0.368 (t = 8.745; p = 0.000). Bureaucratic accountability also significantly affects public trust, with a regression coefficient of 0.412 (t = 9.832; p = 0.000). Simultaneously, both variables have a significant effect on public trust, with an F value of 187.542 (p = 0.000) and an R² of 48.6%. The findings suggest that bureaucratic accountability plays a more dominant role than e government in shaping public trust. This study recommends a synergy between the development of digital systems and strengthening accountability practices to enhance public service quality and increase trust in local governments.